Pembuatan Aplikasi Permainan Edukasi Tentang Hewan Berdasarkan Jenis Makanannya Berbasis Android - Jeremia Borichlev; Harya Bima Dirgantara (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this research is to create an alternative learning in which ordinary people (all ages) can learn about animal classification based on food.The game was developed so that users can use alternative media such as smart phones to understand the classification of animals based on their food. The method used in game development is Game Development Life Cycle (GDLC). There are 6 stages of the GDLC method the initiation stage that discusses the concept of the game, the pre-production stage that discusses the design of the game, the production stage of the game development using the Unity game engine, the testing phase to test the game's functionality with the blackbox method, the beta testing stage for the user and the release stage the game to the public. The final result of this study is an Android-based "Animal-Based Food Quiz" educational game that is played offline on smart phones. One of the results of the beta testing was 88% (22 respondents) out of 25 respondents had a better understanding of animal classification based on food after playing this game.